2022
DOI: 10.1155/2022/9527576
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Antenatal Care Service Satisfaction among Women in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Background. Antenatal care service satisfaction is a measure of the degree to which a woman seeking care is happy with the antenatal care service provided to her. Thus, this systematic review and meta-analysis aims to identify factors that determine antenatal care service satisfaction among women in Ethiopia. Methods. PubMed, Hinari, and Google Scholar were systematically searched for eligible studies. In addition, national university digital libraries were also searched. The Joanna Briggs Institute’s (JBI) cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Although we have no data on client perceptions of how they were treated, most reported satisfaction with provider communication. However, a multicountry meta-analysis found that the first ANC visit was associated with greater client satisfaction 30 ; by targeting new ANC clients, MSDQI may overestimate client satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have no data on client perceptions of how they were treated, most reported satisfaction with provider communication. However, a multicountry meta-analysis found that the first ANC visit was associated with greater client satisfaction 30 ; by targeting new ANC clients, MSDQI may overestimate client satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…According to [20], concerns were made about the staff members' lack of courtesy. A further obstacle that has been identified as discouraging pregnant women from accessing ANC is the staff members' disrespect towards them [22]. As such, midwives should welcome pregnant women positively and use the appointment system to commence making amends.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction with antenatal care services is affected by different dimensions such as structure (physical environment and availability of adequate human resources, medicines, and supplies), process (interpersonal behavior, privacy, promptness, cognitive care, perceived provider competency, and emotional support), and outcome (health status of the mother and fetus) [19]. It is also associated with sex of the health-care provider; the religion, educational status, residence, ethnicity, and age of the mother; history of antenatal care; waiting time; transportation; distance of health facility from home; type of pregnancy; and history of abortion [19][20][21][22][23][24].…”
Section: Literature Review 21 Overview Of Antenatal Care Servicesmentioning
confidence: 99%
“…Satisfaction with antenatal care services among pregnant women at different parts of Ethiopia ranges from 33.4% to 83.9% [23]. This shows that the quality of antenatal care services is inconsistent and varied.…”
Section: Literature Review 21 Overview Of Antenatal Care Servicesmentioning
confidence: 99%